Re-Layout Of STNK Annual Tax Payment At The XXX Samsat Office By Promodel Simulation - Tombak Gapura Bhagya (Sainteks: Jurnal Sain dan Teknik, 2022)
Re-layout is an action that requires a large amount of money if done manually. So it is necessary to use technology to minimize the cost of re-layout. Simulation is one solution that can be applied in solving problems related to layout improvement. The SAMSAT XXX office experienced a very heavy queuing problem, so it was necessary to improve the layout by changing the position of the service office. By using the modeling system, the STNK tax service system can be created in a virtual system and a new layout is created using the promodel. The results indicate the need for additional registration counters from the initial one consisting of only one counter to three counters, and this has the effect of increasing the productivity of payment counters and delivery counters by up to 15%. So that the productivity burden of the three counters at the SAMSAT XXX office has the same load.